Inflammatory Phase Perineal Wound Healing on Postpartum Mothers: Effects of Boiled Eggs and Snakehead Fish Administration - Yuliani Budiyarti; Livia Mahda (Universitas Muhammadiyah Tangerang, 2023)
The infection can cause the death of 1 in 10 mothers undergoing the postpartum period. This is partly due to the wound that occurs in the perineum, where the wound does not dry easily, so it is at risk of increasing the incidence of infection. The aim of the study was to analyze the differences in the effectiveness of giving boiled eggs and snakehead fish to the healing of perineal wounds in the inflammatory phase in postpartum mothers. This type of quantitative research with a quasi-experimental non-equivalent group design. Sampling used a purposive sampling technique with the criteria of postpartum mothers on the first day who experienced second-degree perineal injuries, aged 20-35 years, had good personal hygiene and did not experience complications. The number of samples was 30 people, divided into two groups, which are group 1 with the administering of 2 boiled eggs (100g) and group 2 with the administering snakehead fish (50g), the administration time was 5 days. Analysis test using Wilcoxon and Mann Whitney. The results of the Wilcoxon test ρ value 0.000, so that there is an effect of giving boiled eggs and snakehead fish on the process of healing perineal wounds in the inflammatory phase with an average duration of 4 days and the Mann Whitney test with ρ value 0.417 where there is no difference in effectiveness between the two. Boiled eggs and snakehead fish are both effective for consumption to help the healing process of the inflammatory phase of the perineal wound.